Kinerja Dinas Pendidikan Pemuda dan Olahraga dalam Program Wajib Belajar Sembilan Tahun di Kabupaten Siau Tagulandang Biaro - Riangkamang, Jhon Handri; Pangkey, Masje Silija; Londa, Very (Sam Ratulangi University, 2016)
Abstract: Education is a key to reducing poverty in the medium and long term and one of the mostimportant elements in national development, because with education for the community to be promisingpeople more advanced in his thinking. Thought developed societies to form a Human Resources (HR) ofhigh quality. in the District of Siau Tagulandang Biaro of school age who have not been able to get aneducation, in junior high school education who do not finish school amounted to 51 students from thedata taken at the Department of Education Youth and Sports District Siau Tagulandang Biaro. The causeof the children who dropped out of school As well as some elementary school and junior high school inthe district of Siau Tagulandang Biaro still not being prasyrarat terselenggaraya education among othersdamaged classrooms and the uneven ketersebaran teachers is a problem facing education in the DistrictSiau Taguladang Biaro. Conditions as described previously prompted the authors to determine the depthon the performance of the Department of Education, Youth and Sports District Siau Tagulandang Biaroin implementing the nine-year compulsory education program. From the results of research and analysisconcluded that the Performance Department of Education Youth and Sport in the Nine-Year CompulsoryEducation Program which terihat on five aspects, namely. Productivity, quality of service,responsiveness, responsibility and accountability. Of the five aspects of the new aspects that have goodresponsiveness in responding to community needs its citizens basic education, especially primary schooldropouts and facilitate the higher education level, and an increase in APM elementary and junior highschool through the nine-year compulsory education programKeywords: Performance, Organizational Performance, nine-year compulsory education